Most common ophthalmic diagnoses in eye emergency departments: a multicenter study - Mahjoub, Heba; Ssekasanvu, Joseph; Yonekawa, Yoshihiro; Justin, Grant A.; Cavuoto, Kara M.; Lorch, Alice; Madan, Vrinda; Sivakumar, Ishu; Zhao, Xiyu; Quintero, Michael; Simeon, Olivia Febles; Salabati, Mirataollah; et al. (Digital Journal of Ophthalmology, 2024)
Introduction Ocular emergencies comprise roughly 1.5% of visits across US emergency departments (EDs) every year, but education covering ophthalmic conditions is often lacking, beginning at the medical student level. Appropriately assessing and treating these ocular emergencies is imperative to prevent permanent, long-term vision loss. Purpose To characterize the most common ophthalmic conditions seen in the emergency department (ED) Methods Multicenter, cross-sectional study of 64988 patients who visited the Bascom Palmer Eye Institute, Massachusetts Eye and Ear, Wills Eye Hospital, Johns Hopkins Hospital/Wilmer Eye Institute from January 1, 2019, until December 31, 2019. Demographic and primary diagnosis data was extracted including gender, age, race, ethnicity, insurance type, and ophthalmology consult status. Descriptive statistics were performed on all data using STATA IC 14 (64-bit). Results A total of 64988 patients with primary ocular diagnoses were seen across all four EDs. The majority of patients were White (63.1%), non-Hispanic/Latino (64.8%), and female (52.3%). The most frequently seen age group was 50-64 years (28.6%). The most common diagnoses across all institutions were conjunctivitides (7.91%), corneal abrasions (5.61%), dry eye (4.49%), posterior vitreous detachments (4.15%), chalazions (3.71%), corneal ulcers (3.01%), subconjunctival hemorrhages (2.96%), corneal foreign bodies (2.94%), retinal detachments (2.51%), and glaucoma (2.12%). Specifically, viral conjunctivitis (2283/5139, 44.4%) and primary open angle glaucoma (382/1379, 27.7%) were the most frequently seen subtypes of conjunctivitis and glaucoma. Conclusions The most regularly treated ophthalmic conditions in high volume EDs tend to be lower acuity diagnoses. To combat ED overcrowding and rising health care costs in the United States, we suggest diverting eye-related ED visits to a specialized eye ED service or same-day eye clinic appointment in addition to expanding education for patients and primary care clinicians.